Looking deep at current research information systems - Fernandes, Sofia (Qualitative and Quantitative Methods in Libraries, 2019)
The objective of this paper is to present and discuss a project that is being developed to implement a Current Research Information System (CRIS) in a Higher Education Institution (HEI). This article discusses the various steps that are being followed to design, define and implement a CRIS system, while at the same time presenting a comparative study between two commercially available CRIS solutions and a Dspace CRIS, highlighting the most common key features that should make part of such a R&D management and support system. Implementing a CRIS in a HEI requires a methodology plan that takes into consideration all the institutional, technological and organizational restrictions and requirements, and in this paper we share an Information Management perspective on this challenge, where the main concern is being able to help design and develop an optimized and efficient R&D managing system that fosters and leverages research results and their worldwide dissemination and visibility